Urgensi Nilai-NilaUrgensi Nilai-Nilai Pancasila Bagi Pejabat Pemerintahan Dalam Upaya Pencegahan Korupsi Di Indonesiai Pancasila Bagi Pejabat Pemerintahan Dalam Upaya Pencegahan Korupsi Di Indonesia - Julianus Maukoni, Alexander; Adi Saingo, Yakobus (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Corruption is a disgraceful act that still occurs today involving unscrupulous government officials in Indonesia because they have not been able to implement the values ​​of Pancasila completely and comprehensively. The aim of this research is the urgency of Pancasila values ​​for government officials in efforts to prevent corruption in Indonesia. This research uses a literature study method by reading various information related to the research topic from scientific literature and stating it in writing in accordance with scientific study procedures. The data was analyzed descriptively by showing the results that instilling the values ​​of Pancasila is very important and urgent considering that until now corrupt behavior is still difficult to prevent and these actions still occur massively in social life, which often also involves unscrupulous government officials. The values ​​of Pancasila must be lived fully and comprehensively by every government official by seriously practicing the values ​​of divinity, humanity, unity, democracy and social justice. Acts of corruption committed by unscrupulous government officials have harmed the existence of the Indonesian nation and state because they violate the values ​​of Pancasila. For this reason, efforts to prevent acts of corruption can be carried out from an early age by instilling Pancasila values ​​starting from the family environment, education, workplace institutions and anti-corruption community organizations.